THE RISE AND FALL OF GLASS-STEAGALL - Kenneth Weiher (Essays in Economic and Business History, 2001)
The passage of the Financial Services Modernization Act in 1999 was saidto have finally repealed the Glass-Steagall Act. In 1933, Congress enacted a set of bank regulations entitled of The Banking Act of 1933 (more commonly known as the Glass-Steagall Act) which created an array of new bank structures and restrictions, including: 1. the prohibition and limitations of deposit interest payments, 2. the separation of commercial from investment banking, and 3. the creation of FDIC. Furthermore, the new legislation chose to reaffirm the restrictions on interstate branch banking. The composite of these four provisions formed an environment in which banks operated for decades, until one after another these restrictions were strippedaway until the passage of the FSMA left only FDIC as the last major component still standing. This paper examines the four provisions and reviews the literature in terms of: a. the rationale behind each provision, b. the theoretical and empirical evidence about the wisdom of the rationale, c. the ultimate impact of the provision on the banking industry and d. the reason why all but FDIC have been repealed.